Observation of antioxidant activity of leaves, callus and suspension culture of Justicia gendarusa - Amid, Azura; Johan, Nurul Najwa; Jamal, Parveen; Wan Mohd Zain, Wan Norzaidani (Academic Journals, 2011)

(untitled)
Antioxidant activity and phenolic compound was found in Justicia gendarussa via total phenolic content (TPC) and ,-diphenyl--pycrilhydrazil hydrate (DPPH) radical scavenging assays. The assays were applied on aqueous and methanolic extracts of leaves, callus culture and cell suspension culture of J. gendarussa. Callus was induced from green and matured leaves of J. gendarussa cultured on Murashige and Skoog (MS) basal medium supplemented with different concentrations of 2,4- dichlorophenoxyacetic acid (2,4-D) or 1-naphthaleneacetic acid (NAA) and benzylaminopurine (BAP). Callus induced on NAA showed higher phenolic content and antioxidant activity as compared to the one induced on 2,4-D. The highest total phenolic content (88 mg GAE/g) was observed in callus culture induced with NAA and BAP, while the highest antioxidant activity (lowest IC50; 8.46 × 10-3mg/ml) was observed in the cell suspension.